Sacred stories, spiritual tribes : finding religion in everyday life - Ammerman, Nancy Tatom, 1950- (Oxford University Press, 2013)
Nancy Tatom Ammerman examines the stories Americans tell of their everyday lives, from dinner table to office and shopping mall to doctor's office, about the things that matter most to them and the routines they take for granted, and the times and places where the everyday and ordinary meet the spiritual.
Keywords: Spirituality -- United States.; Religion.; United States -- Religious life and customs.; Religion; Spiritualité -- États-Unis.; religion (discipline); SOCIAL SCIENCE -- Sociology of Religion.; Spirituality; United States; Spirituality -- Religion. -- United States.